Learning Basic Grammar Using Task-Based Learning: A Perspective on Analyzing Online Media Text - Dwi Astuti Wahyu Nurhayati (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This paper displayed the perspective on analyzing online media text using task-based learning in learning basic grammar. The data were collected for 6 months through observation, interview and questionnaires from July to December 2018 in IAIN Tulungagung. It involves 45 Indonesian undergraduate students who were taking English Basic Grammar with online media text. The data was analyzed using a descriptive qualitative approach. The finding revealed that the students got experience of using online media text as learning basic grammar medium. Their perspectives on analyzing online media text using task-based learning are various (not interesting, passive in the learning process, low interest in reading, tend to rely on friends, and difficult to analyze the online text). Furthermore, their’ perspective of using task-based learning in learning Basic English Grammar can be categorized into five types: the act of acquring strategy, the experiencing process, the process of acquiring benefits, the pupils’ responses, and evaluating their performance. It also reported that some benefits of task-based instruction strategy in teaching learning Basic English Grammar can be ability to deep understanding the materials, having good cooperation, having the ability to memorize, managing the time effectively, identifying the kinds of grammar part, and increasing the communication abilities. While the disadvantages of task-based learning in learning Basic English Grammar through analyzing the online media text included having difficulties in analyzing, not being used to with the learning model, getting bored and uncomfortable with the strategy, and being burdened with the task.